2017
DOI: 10.1097/opx.0000000000001047
|View full text |Cite
|
Sign up to set email alerts
|

fMRI with Central Vision Loss: Effects of Fixation Locus and Stimulus Type

Abstract: The observed results suggest that naturalistic images are more likely to trigger top-down processes that regulate activation in early visual cortex in patients with central vision loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…-Oculomotor training, mainly aimed at the use of a PRL to obtain stability in eccentric fixation, has a positive effect on the performances obtained in the visual task (Plank et al, 2014). These effects are accompanied both by structural changes in the cerebellum (Rosengarth et al, 2013) and by interesting functional changes, where PRL stimulation generates a response of the LPZ, and greater fixation stability corresponds to a greater consequent activation (Plank et al, 2017). -In multiple occasions, PRL stimulation was investigated: in patients using PRL for visual elaboration, its stimulation has proven to trigger a more extensive visual cortical activation than in patients not using it (Plank et al, 2013); in particular, stimulation of the PRL was able in some studies to activate that very cortical area normally receiving input from the lesioned macula (Baker et al, 2008;Masuda et al, 2008;Schumacher et al, 2008;Plank et al, 2017) but not in all of them (Liu et al, 2010).…”
Section: Analysis Of Functional Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…-Oculomotor training, mainly aimed at the use of a PRL to obtain stability in eccentric fixation, has a positive effect on the performances obtained in the visual task (Plank et al, 2014). These effects are accompanied both by structural changes in the cerebellum (Rosengarth et al, 2013) and by interesting functional changes, where PRL stimulation generates a response of the LPZ, and greater fixation stability corresponds to a greater consequent activation (Plank et al, 2017). -In multiple occasions, PRL stimulation was investigated: in patients using PRL for visual elaboration, its stimulation has proven to trigger a more extensive visual cortical activation than in patients not using it (Plank et al, 2013); in particular, stimulation of the PRL was able in some studies to activate that very cortical area normally receiving input from the lesioned macula (Baker et al, 2008;Masuda et al, 2008;Schumacher et al, 2008;Plank et al, 2017) but not in all of them (Liu et al, 2010).…”
Section: Analysis Of Functional Resultsmentioning
confidence: 99%
“…It should be noted that there is one study that did not detect the activation of LPZ by the PRL by using only passive visual stimuli, without visual task. -The nature of the stimulus seems also to influence brain response (Plank et al, 2017): object pictures were found to elicit stronger responses of the central representation area in the visual cortex than did the flickering checkerboard, probably due to feedback projections from higher visual areas. -Finally, against the hypothesis of remodeling, it was pointed out by Haak et al (2016) that a retinotopic organization of the visual cortex has proven to persist although long after the deafferentation generated by AMD, even if decreased in comparison to healthy controls.…”
Section: Analysis Of Functional Resultsmentioning
confidence: 99%
See 3 more Smart Citations